Spin Canting Promoted Manipulation of Exchange Bias in a Perpendicular Coupled Fe3GaTe2/CrSBr Magnetic van der Waals Heterostructure - Ni, Kaipeng; Zhou, Jiayuan; Chen, Yang; Cheng, Huanghuang; Cao, Ziyi; Guo, Junming; Söll, Aljoscha; Hou, Xingyuan; Shan, Lei; Sofer, Zdenek; Yang, Mengmeng; Yue, Yang; et al. (ACS nano, 2025)
Recently, two-dimensional (2D) van der Waals (vdW) magnetic materials have emerged as a promising platform for studying exchange bias (EB) phenomena due to their atomically flat surfaces and highly versatile stacking configurations. Although complex spin configurations between 2D vdW interfaces introduce challenges in understanding their underlying mechanisms, they can offer more possibilities in realizing effective manipulations. In this study, we present a spin-orthogonal arranged 2D Fe3GaTe2 (FGaT)/CrSBr vdW heterostructure, realizing the EB effect with the bias field as large as 1730 Oe at 2 K. Interestingly, this structure induces a positive EB under low cooling field, in contrast to conventional phenomena. Moreover, by employing asymmetric field sweeping methods, we effectively manipulate the zero-field cooling EB of the device with a switchable sign and a tunable magnitude. Thus, these findings not only elucidate a distinct mechanism analysis for EB phenomena with perpendicular coupled spin configurations but also hold promise for promoting contemporary 2D spintronic device applications.
Keywords: spin canting; exchange bias effects; two-dimensional materials; spin-orthogonal FM/AFM heterostructures; asymmetric field sweep